Ion Channels and Electrophysiological Properties of Astrocytes: Implications for Emergent Stimulation Technologies - McNeill, Jessica; Rudyk, Christopher; Hildebrand, Michael E.; Salmaso, Natalina (Frontiers in Cellular Neuroscience, 2021)
Astrocytes comprise a heterogeneous cell population characterized by distinct morphologies, protein expression and function. Unlike neurons, astrocytes do not generate action potentials, however they are electrically dynamic cells with extensive electrophysiological heterogeneity and diversity. Astrocytes are hyperpolarized cells with low membrane resistance. They are heavily involved in the modulation of K+, and express an array of different voltage-dependent and voltage-independent channels to help with this ion regulation. In addition to these K+ channels, astrocytes also express several different types of Na+ channels; intracellular Na+ signaling in astrocytes has been linked to some of their functional properties. The physiological hallmark of astrocytes is their extensive intracellular Ca2+ signaling cascades, which vary at the regional, subregional and cellular level. In this review, we highlight the physiological properties of astrocytes and the implications for their function and influence of network and synaptic activity. Furthermore, we discuss the implications of these differences in the context of optogenetic and DREADD experiments, and consider whether these tools represent physiologically relevant techniques for the interrogation of astrocyte function.